The prevalence of Brodie bite in untreated orthodontic patients in Nigeria - Idia N Ize-Iyamu; Joseph N Otaren (Journal of Orthodontic Science, 2023)
OBJECTIVE: The Brodie bite (BRB) is a rare posterior crossbite affecting the transverse occlusal relationship with the palatal cusps of the upper molars, biting into the vestibule and outside the buccal cusps of the lower molar teeth. The BRB is a highly challenging orthodontic problem and is an extreme form of scissors bite. Patients with this problem present with facial deformity and inability to chew on the affected side. The problem is usually not identified until it becomes severe. This study aimed to identify the prevalence of BRB among untreated orthodontic patients in two geo-political zones in Nigeria. METHODS: A total of 1,041 untreated orthodontic patients who presented to two different orthodontic centres located in two geo-political zones (South/South-Benin City and North Central-Abuja, Nigeria) over a 3-year period were evaluated for the presence of BRB. The transverse dimension of the occlusion was examined for the presence of a crossbite or scissors bite. The molar teeth were used as the reference point for occlusion with Angle's classification of malocclusion. Four groups were identified, namely, teeth in occlusion (TIO) (Angle's Classes I, II or III malocclusion served as the control group), scissors or lingual crossbite (LCB), buccal crossbite (BCB) and BRB. A posterior crossbite was confirmed when the upper molar teeth were biting outside the buccal groove of the lower molar teeth either lingually or buccally. A BRB was identified when the palatal cusps of the upper molars were biting into the buccal vestibule of the lower jaw, with the deviation of the face to that side. Statistical analyses were performed using SPSS version 21; frequencies were determined for the variables, and cross-tabulations between the variables were established. P values < 0.05 were considered significant. RESULTS: The overall prevalence of BRB in this study was 0.6% (six patients). The values in the South/South (Benin City) were 997 untreated orthodontic patients, with a prevalence of 0.5% (five patients). The North Central (Abuja) zone had a total of 44 untreated orthodontic patients, with a prevalence of 2.3% (one patient). Unilateral BRB was seen in five patients (80%), and bilateral BRB was seen in one patient (20%). The condition was more prevalent among women (four patients, 80%) and on the right side (three patients, 60%). Angle's relationship in Classes I, II and III (TIO or control group) was seen in 911 patients (87.5%). The LCB and BCB groups comprised 39 (3.8%) and 85 patients (8.1%), respectively. Posterior crossbite was seen in 130 patients (12.5%). CONCLUSION: The prevalence of BRB in this study was found to be 0.6%, with the condition being more prevalent in women and on the right side.